Find the first partial derivative of
f(w, x, y, z) = w ^ 2 * x * y ^ 2 + x * y ^ 3 * z ^ 2
"\\frac{\\partial f}{\\partial x}(x,y,z,w)=\\frac{\\partial (x\\cdot y^2\\cdot w^2+x\\cdot y^3\\cdot z^2)}{\\partial x}=\\\\"
"\\frac{\\partial (x\\cdot y^2\\cdot w^2)}{\\partial x}+\n\\frac{\\partial (x\\cdot y^3\\cdot z^2)}{\\partial x}=y^2\\cdot w^2\\cdot \\frac{\\partial x}{\\partial x}+y^3\\cdot z^2\\cdot \\frac{\\partial x}{\\partial x}=y^2\\cdot w^2\\cdot 1+y^3\\cdot z^2\\cdot 1=\\\\\n=y^2\\cdot w^2+y^3\\cdot z^2"
"\\frac{\\partial f}{\\partial y}(x,y,z,w)=\\frac{\\partial (x\\cdot y^2\\cdot w^2+x\\cdot y^3\\cdot z^2)}{\\partial y}=\\\\"
"=\\frac{\\partial (x\\cdot y^2\\cdot w^2)}{\\partial y}+\n\\frac{\\partial (x\\cdot y^3\\cdot z^2)}{\\partial y}=x\\cdot w^2\\cdot \\frac{\\partial y^2}{\\partial x}+x\\cdot z^2\\cdot \\frac{\\partial y^3}{\\partial y}=x\\cdot w^2\\cdot (2y)+x\\cdot z^2\\cdot (3y^2)=\\\\\n=2\\cdot x\\cdot y \\cdot w^2+3\\cdot x\\cdot y^2\\cdot z^2"
"\\frac{\\partial f}{\\partial z}(x,y,z,w)=\\frac{\\partial (x\\cdot y^2\\cdot w^2+x\\cdot y^3\\cdot z^2)}{\\partial z}=\\\\"
"\\frac{\\partial (x\\cdot y^2\\cdot w^2)}{\\partial z}+\n\\frac{\\partial (x\\cdot y^3\\cdot z^2)}{\\partial z}=0+x\\cdot y^3\\cdot \\frac{\\partial z^2}{\\partial z}=x\\cdot y^3\\cdot(2z)=2\\cdot x\\cdot y^3\\cdot z"
"\\frac{\\partial f}{\\partial w}(x,y,z,w)=\\frac{\\partial (x\\cdot y^2\\cdot w^2+x\\cdot y^3\\cdot z^2)}{\\partial w}=\\\\"
"\\frac{\\partial (x\\cdot y^2\\cdot w^2)}{\\partial w}+\n\\frac{\\partial (x\\cdot y^3\\cdot z^2)}{\\partial w}=x\\cdot y^2\\cdot \\frac{\\partial w^2}{\\partial w}+0=x\\cdot y^2\\cdot (2w)=2\\cdot x\\cdot y^2\\cdot w"
Comments
Leave a comment